Cost-Effectiveness of Eplerenone Compared to Usual Care in Patients With Chronic Heart Failure and NYHA Class II Symptoms, an Australian Perspective - Ademi, Zanfina (Medicine (Baltimore), 2016)
The objective of this study was to determine the cost-effectiveness of eplerenone compared with usual care in patients with chronic heart failure and New York Heart Association (NYHA) Class II symptoms. A Markov model was constructed with 5 health states to reflect NYHA symptom status (Classes I–IV) and death. All subjects began in the “Class II” health state and then moved to other symptom health states or died. Subjects could also be hospitalized for HF in any cycle. Transition probabilities were derived from the Eplerenone in Mild Patients Hospitalization And Survival Study in Heart Failure (EMPHASIS-HF) study. Decision analysis was applied to compare an Eplerenone Group with a Usual Care Group (UCG). In the UCG, 47.3% of subjects in Class II and 93.7% of subjects in Classes III and IV were assumed to be taking spironolactone (as per published data). In the Eplerenone Group, all subjects in Classes II, III, and IV were assumed to be taking eplerenone. The efficacy of spironolactone was assumed to be the same as eplerenone. Cost and utility data were derived from published sources. A discount rate of 5.0% was applied to future costs and benefits. The outcome of interest was incremental cost-effectiveness ratio (ICER) (cost per year of live saved (YoLS) and quality-adjusted life years (QALY) gained). Over 10 years the model predicted that for each patient compared with usual care, eplerenone would lead to 0.26 YoLS (discounted) and 0.19 QALYs gained (discounted), at a net cost of AUD $6961 (discounted). These equate to ICERs of AUD 28,001 per YoLS and AUD 37,452 per QALY gained. Sensitivity analyses indicated a 99.0% likelihood of eplerenone being cost-effective compared with usual care at a willingness to pay threshold of AUD 50,000 per QALY gained. From an Australian healthcare perspective, the addition of eplerenone in management of patients with chronic heart failure and NYHA Class II symptoms represents a cost-effective strategy compared with usual care.